Novel rare variants in FGFR1 and clinical characteristics analysis in a series of congenital hypogonadotropic hypogonadism patients. (30th April 2021) - Nie, Min; Yu, Bingqing; Chen, Rongrong; Sun, Bang; Mao, Jiangfeng; Wang, Xi; Zhang, Hongbing; Wu, Xueyan
Abstract: Objective: We aimed to analyse FGFR1 rare variants in a series of Chinese congenital hypogonadotropic hypogonadism (CHH) patients. In addition, we intended to understand the clinical characteristics and the response to treatment of CHH patients with FGFR1 rare variants. Patients and Methods: A total of 357 CHH patients were recruited at Peking Union Medical College Hospital. We used Sanger sequencing to analyse FGFR1 gene. In silico analysis was carried out to study the pathogenicity of novel missense variants. The clinical, endocrinological and therapeutic effects from patients carrying FGFR1 rare variants were analysed retrospectively. Results: Thimissense mutations.rty patients in this series were found to harbour 29 FGFR1 rare variants, with 8 recurrent and 21 novel variants. After comprehensive analysis, 18 out of 21 novel variants were classified as likely pathogenic (LP) ones. These variants are widely spread throughout the FGFR1 gene and almost all FGFR1 functional domains, which exhibited no hot spot. Cryptorchidism, cleft palate and dental abnormality incidence in this CHH series that possessed FGFR1 LP variants were approximately 38.5%, 7.6% and 3.8%, respectively. Among patients who accepted the fertility‐promoting treatment, 8 out of 10 patients succeeded in spermatogenesis. Conclusions: Eighteen novel LP variants were found to expand the spectrum of FGFR1 rare variants. In CHH patients possessing FGFR1 variants, we found that the rate of spermatogenesis was high following fertility‐promoting therapy and the existence of cryptorchidism may represent the underlying factors which affect spermatogenesis.